Euro area sovereign yield spreads as determinants of private sector borrowing costs - Theobald, Thomas; Tober, Silke (Economic modelling, 2020)
We regress long-term private-sector borrowing rates on a money market rate, a term premium and credit risk. As a contribution to the current debate about European safe assets, our interest is in quantifying the impact of euro area sovereign bond spreads on private-sector lending by employing it as a proxy for private-sector credit risk. Panel estimates show significant, albeit rather small long-run effects. Another finding is large cross-country heterogeneity. Using linear country-specific estimates, we find the effect to be significant in only some countries, but the size of the maximum effect in these countries exceeds the average one more than three-fold. Furthermore, for one country, we find an asymmetrical effect with positive spread changes having greater impact on private-sector borrowing costs than negative ones. Substantial heterogeneity of the spillover effect between euro area countries indicates the presence of financial valuation effects based not only on economic fundamentals. This, in turn, implies that spillovers may entail contagion costs. Overall, our results suggest that these costs are considerable in the euro area and will remain so until an effective form of European safe assets is created. •We find significant evidence for domestic spill-over effects from euro area sovereign bond spreads to private sector borrowing rates.•Spill-overs subject to financial market valuation confirm the benchmark function of sovereign bonds in asset pricing.•Our findings underlines the need for an effective safe-asset construction in the euro area (Lane, 2012)